FINITE ELEMENT ANALYSIS OF COMPOSITE SPUR GEAR - Devi S, Mrs.S.Kousalya (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
In this project, an attempt has been made to design, model and finite element analysis of spur gear using composite material. Conventional spur gears are made up of cast iron or mild steel. Composite material could be an alternative for conventional materials considering the advantage of less weight, rust formation and less maintenance. Modeling of spur gear is done using solid works and finite element analysis is done in Ansys. Based on the analysis results it is suggested that short carbon reinforced (SCF) nylon to be used in place of cast iron or mild steel for limited load applications under 1500 watts.